Improving global financial services regulation - Shanker A. Singham; Catherine McBride (Institute of Economic Affairs (IEA), 2018)
As the most globally active financial services provider, the UK has the potential to be a key player in helping to develop a more efficient international regulatory framework after it leaves the EU. All entities that have efficient and attractive financial services offerings will benefit from having better global financial services regulation. The UK financial services industry is a major component of its economy. In 2016, UK financial services contributed 6.7% of the total UK GVA1, provided 3.1% of all jobs in the UK and generated a trade surplus of 68bn2 in the finance and insurance sectors.
Keywords: L51; G18; G28; G38; G15; F36; 330